Aplikasi residu biochar sekam padi dan pupuk NPK terhadap pertumbuhan dan produksi rumput Meksiko (Euchlaena mexicana) pada tahun kedua - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
This study aims to determine the effect of combined dose of biochar residue from rice husk and NPK fertilizer on growth and production of Mexican grass (Euchlaena mexicana) in the second year and to determine the combination dose of biochar residue of rice husk and NPK fertilizer which gives the best results on the growth and production of grass Mexico in the second year. This study was designed using a Completely Randomized Design (CRD) with a single treatment of various doses of residual combination of rice husk biochar and NPK fertilizer (B) with 5 replications, namely b0 = 0 without biochar rice husk and NPK fertilizer (control), b1 = 5 tons ha -1 residue of rice husk biochar + 75% recommended dosage, b2 = 10 tons ha-1 rice husk biochar residue + 50% recommended dose and b3 = 15 tons ha-1 wood biochar + 5 tons ha-1 cow manure. The results of this study are that the combination dosage of rice husk biochar residues and NPK fertilizer does not affect the growth and production of Mexican grass in the second year. Keywords : Applications, rice husk biochar residues, production